Shocks, cooling and the origin of star formation rates in spiral galaxies - Bonnell, Ian; Dobbs, Clare; Smith, Rowan J. (Monthly notices of the Royal Astronomical Society, 2013)
Abstract. Understanding star formation is problematic as it originates in the large-scale dynamics of a galaxy but occurs on the small scale of an individual st